From Accelerated Accumulation to the Socialist Market Economy in China: Economic Discourse and Development from 1953 to the Present - Kjeld Erik Brødsgaard; Koen Rutten (Brill, 2017)
The book is based on the hypothesis that a systematic analysis of the Chinese economic discourse is necessary in order to understand the underlying logic of Chinese economic development.~The majority of works on the subject see China's economic development as a linear process of marketization or "growing out of the plan". In contradistinction to the prevailing paradigm, this book underlines that basic economic issues such as over-investment and unbalanced development continue to frame economic policy-making. The book is also unique in basing the narrative on a rich collection of Chinese language material.
Keywords: 330; History; Ecomomics; Asian Studies